Brecht, Turkish theater, and Turkish-German literature : reception, adaptation, and innovation after 1960 - Gezen, Ela E., 1977- (Studies in German literature, linguistics, and culture., 2018)
Uncovers the central role of Brecht reception in Turkish theater and Turkish-German literature, examining interactions between Turkish and German writers, texts, and contexts.